Refugee Families With Children With Disabilities: Exploring Their Social Network and Support Needs. A Good Practice Example - Bešić, Edvina; Hochgatterer, Lea (Frontiers in Education, 2020)
This study focuses on caregivers from refugee backgrounds who have children with disabilities. By concentrating on the support role of social networks, it explores how caregivers navigated the Austrian social support system. Semi-structured interviews with three caregivers and five service providers (including parents' guides: Elternlotsinnen) for migrant families with children with disabilities were conducted. The findings reveal not only particular challenges—for example, displaced children with disabilities not receiving adequate support from social providers—but they also allude to certain good practices. Results demonstrate that one organization, that finds itself at the intersection of migration and disability, improved the knowledge about the support system for these caregivers.